Chiral microenvironment-responsive mesoporous silica nanoparticles for delivering indometacin with chiral recognition function. (February 2022) - Gou, Kaijun; Guo, Xianmou; Wang, Yuxin; Wang, Yumei; Sang, Zhentao; Ma, Shuangshuang; Guo, Yingyu; Xie, Linlin; Li, Sanming; Li, Heran
Graphical abstract: Highlights: The novel chiral silicon coupling agents (TESPSA-L/D-Pro) were prepared successfully. Chiral microenvironment-responsive mesoporous silica nanoparticles (CMR-L/D-MSN) with molecular-level chirality were prepared successfully. CMR-L/D-MSN had high specific surface area and exhibited the potential the chiral recognition function. CMR-D-MSN had higher bioavailability and stronger anti-inflammatory effect for delivering IMC compare with CMR-L-MSN. Abstract: The purpose of this study was to investigate the potential chiral recognition functions induced by two kinds of novel chiral microenvironment-responsive mesoporous silica nanoparticles (CMR-L-MSN and CMR-D-MSN) for the oral delivery of the poorly water-soluble achiral drug indomethacin (IMC). The as-synthesized CMR-L-MSN and CMR-D-MSN with molecular chirality and high specific surface area (SBET : 1141 and 1075 m 2 /g, respectively) were successfully prepared through grafting chiral molecular functional groups. The characterization results showed that CMR-L-MSN and CMR-D-MSN were spherical nanoparticles with opposite chiral features and clearly visible pore channels. Meanwhile, they exhibited good biosafety and degradability. In vitro drug release study indicated that both CMR-L-MSN and CMR-D-MSN significantly improved IMC dissolution compared with naked-MSN (N-MSN) ( p < 0.05) and exhibited different chiral recognition functions for drug release in the simulated chiral environments in vitro (pH 6.8 PBS-D/L), in which CMR-D-MSN could be triggered by the L-configurations in chiral environments and exhibited a better drug release effect. As expect, the results of in vivo biological effects disclosed that CMR-D-MSN had higher bioavailability of IMC and obvious advantages on drug adsorption and in vivo distribution, and exerted stronger anti-inflammatory effect after making specific response to the in vivo chiral environment.